2003
DOI: 10.1002/ana.10789
|View full text |Cite
|
Sign up to set email alerts
|

Febrile seizures impair memory and cAMP response‐element binding protein activation

Abstract: The long-term effects of brief but repetitive febrile seizures (FS) on memory have not been as thoroughly investigated as the impact of single and prolonged seizure in the developing brain. Using a heated-air FS paradigm, we subjected male rat pups to one, three, or nine episodes of brief FS on days 10 to 12 postpartum. Neither hippocampal neuronal damage nor apoptosis was noted within 72 hours after FS, nor was there significant hippocampal neuronal loss, aberrant mossy fiber sprouting, or altered seizure thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
104
3

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 125 publications
(110 citation statements)
references
References 49 publications
3
104
3
Order By: Relevance
“…Rats belonging to the seizure group were individually placed into a 3-l glass cylinder which was partly immersed in a water bath kept at room temperature to help prevent overheating of the walking surface (Chang et al, 2003). A hair dryer at a moderate heat setting (500 W) was used to blow hot air down from the top of the container, ∼50 cm above the head of the rat.…”
Section: Repeated Heated-air (Hyperthermia)-induced Seizuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Rats belonging to the seizure group were individually placed into a 3-l glass cylinder which was partly immersed in a water bath kept at room temperature to help prevent overheating of the walking surface (Chang et al, 2003). A hair dryer at a moderate heat setting (500 W) was used to blow hot air down from the top of the container, ∼50 cm above the head of the rat.…”
Section: Repeated Heated-air (Hyperthermia)-induced Seizuresmentioning
confidence: 99%
“…A hair dryer at a moderate heat setting (500 W) was used to blow hot air down from the top of the container, ∼50 cm above the head of the rat. The ambient air temperature within the container (measured at a height level with the rat's head) was kept between 46 and 49 • C (Chang et al, 2003). Temperature was measured by gentle insertion of a thermometer into the external ear canal before and after each hyperthermia/control session for every rat.…”
Section: Repeated Heated-air (Hyperthermia)-induced Seizuresmentioning
confidence: 99%
See 1 more Smart Citation
“…On P33, following deep anesthesia with an overdose of chloral hydrate 500 mg/kg i.p., rats were killed. The brains and eyes were removed, weighted, fixed, and then embedded in paraffin as described previously (26). After removal of the brainstem and cerebellum, the forebrain was sectioned at the midline, and left and right hemispheric weights were determined.…”
Section: Long-term Outcome Measuresmentioning
confidence: 99%
“…It has been debated whether the seizures and accompany neuronal network hyperexcitability contribute to learning disabilities, since a neuropathology could be responsible for both seizures and cognitive impairments. However, recent studies in normal rodents have shown that experimentally-induced recurrent seizures can lead to spatial learning and memory deficits (Holmes et al, 1998;Huang et al, 1999;Lee et al, 2001;Chang et al, 2003). Reduced dendritic arbors following recurrent seizures would be one potential mechanism underlying such learning deficits given that dendrites are the major site of excitatory synaptic transmission and the plasticity thought to underlie formation of memories.…”
Section: Potential Clinical Implicationsmentioning
confidence: 99%